Abusive Supervision and Suicidal Ideation: The Potential Role of Meaning in Life. Issue 12 (2nd December 2021) - Liu, Yuxin; Gul, Habib; Zhang, Jianwei; Raza, Jamshed; Usman, Muhammad
ABSTRACT: Suicide is a common health concern around the globe. Factors that can enhance suicidal thoughts, which are considered the first phase of suicide, must be identified to address this global issue. Workplace stressors (e.g., abusive supervision) and psychological mechanisms need to be assessed to go beyond the existing risk factors that can enhance suicidal ideation. More importantly, the present study examined meaning in life as a possible moderator and mediator between abusive supervision and suicidal ideation. In the present study, we used a diverse sample of (N = 665) subordinates from six Chinese organizations and split the sample into two (N1 = 332, N2 = 333) based on low suicidal ideation and high suicidal ideation. Our results showed that abusive supervision was significantly associated with suicidal ideation. The regression analysis results indicated that meaning in life moderated and mediated the relationship between abusive supervision and suicidal ideation. Our results indicate that intervention strategies that focus on the meaning in life can be influential in mitigating suicidal ideation in subordinates.